Features of speech behaviour of Kazakhstani youth: sociolinguistic and psycholinguistic aspects of research - Anichshenko, О.А.; Zharkynbekova, Ш.К. (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2024)
The article considers the speech behavior of modern Kazakhstani youth from the point of view of sociolinguistics and psycholinguistics. The concept of “speech behaviour” is interpreted in different ways, and the relevance of its study is substantiated. The importance of studying the sociolinguistic portrait of Kazakhstani youth and its components is argued. The authors of the article reveal the trends reflected in the speech behavior of Kazakhstani youth (tolerance, multiculturalism, identification, desire for knowledge of languages, and peculiar word creation, etc.), characteristic features of mentality. The creation of a special communicative environment among young people in Kazakhstan is emphasized. The results of the study are illustrated by rich linguistic material, among the sources of which scientific and journalistic literature, materials from Internet sites, and long-term observations of live speech communication of young people of our country occupy an important place. The objectives of the study required the use of a comprehensive approach to analyzing the collected material and its sociolinguistic and psycholinguistic interpretation.